Global longitudinal strain and mechanical dispersion at rest in exercise stress echocardiography for detecting obstructive coronary artery disease: a pilot study. (8th February 2021) - Sugito, S; Ferreira, D; Hardy, J; Turner, S; Boyle, A; Cooke, H
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Exercise stress echocardiography (ESE) is a commonly used investigation for risk stratification in coronary artery disease (CAD). The added value of resting indices such as Global Longitudinal Strain (GLS) and Mechanical Dispersion (MD) to detect obstructive CAD is not well established and would be of significant clinical benefit. PURPOSE: To evaluate the diagnostic value of GLS and MD at rest and post-exercise during ESE to detect obstructive CAD, defined by angiographic stenosis >70% in any major coronary artery. METHODS: Retrospective cohort study of 80 consecutive patients who underwent ESE and had coronary angiography (invasive or CT) within 6 months. Retrospective speckle tracking strain analysis was performed on digitally archived video-loops, using vendor independent software. Data on demographics, medications, outcomes and ESE characteristics were collected and analysed. RESULTS: In 49 (61.3%) patients with any CAD >70%, GLS at rest was lower (-13.9% ± 4.2 vs -16.1% ± 5.2, p-value = 0.04), and MD at rest was higher (81ms ± 43 vs 58ms ± 28, p-value = 0.008), when compared to patients without CAD >70%. GLS and MD measured post-exercise were not significantly different between groups. Ejection fraction (EF) and Wall Motion Score Index (WMSI) at rest and post-exercise were not significantly different between groups. A resting GLS cutpoint of -14% had a sensitivity and specificity of 57/68%, comparable to the development of new regional wall motion abnormalities (71/39%) and peak WMSI >1.2 (59/48%). Additionally, in 39 (48.8%) patients who had >70% stenosis in the left anterior descending (LAD) artery, LS in the LAD territory segments was lower (-16.2% ± 4.4 vs -18.3% ± 4.7, p-value = 0.04), when compared to patients without >70% stenosis in the LAD artery. CONCLUSION: Resting GLS was lower and MD higher in patients undergoing ESE, who have any CAD >70% compared to patients who do not have any CAD >70%. Resting GLS and MD may increase diagnostic accuracy during ESE to predict obstructive CAD. Further prospective studies evaluating the utility of resting indices to predict functionally significant CAD are required.